Lobar Cerebral Microbleeds Are Associated With Cognitive Decline in Patients With Type 2 Diabetes Mellitus - Shao, Pengfei; Xu, Hengheng; Sheng, Xiaoning; Qin, Ruomeng; Ma, Junyi; Luo, Yishan; Lee, Allan; Shi, Lin; Huang, Lili; Cheng, Yue; Zhao, Hui; Xu, Yun (Frontiers in Neurology, 2022)
Purpose: Combined the number, volume and location of cerebral microbleeds (CMBs), this study aimed to explore the different features of CMBs and their correlation with cognitive ability in type 2 diabetes mellitus (T2DM) patients. Methods: This study recruited 95 T2DM patients and 80 healthy control (HC) individuals. AccuBrain®, an automated tool, was used to obtain the number and volume of CMBs. The scores on global cognition and five cognitive domains were derived from a battery of cognitive tests. The logistic regression and multivariate linear regression were conducted to determine the relationship between the CMBs (number, volume and location) and cognitive ability in T2DM patients. Results: After adjusting for several variables, the total volume of CMBs (OR= 2.339, 95%CI: 1.118 to 4.893, P =0.024) was independent risk factor for cognitive impairment, while the total number of CMBs was not (OR= 1.081, 95%CI: 1.929 to 1.257, P =0.313). Furthermore, the volume of CMBs in lobar regions was independently associated with working memory (= -0.239, 95%CI: -0.574 to -0.038, P =0.026). However, no significant correlation between the number of CMBs (both lobar and deep / infratentorium) and any cognitive domains was observed. Conclusions: Lobar CMBs was related with cognitive impairment in T2DM patients and might be a potential early warning signal. Compared with counting analysis, quantitative method offered a more sensitive, and objective measurement for studying imaging features of CMBs.